Evaluating the Flame Retardancy of Shaving Super Bamboo Layer by Layer Self-Assembly With Phytic Acid-Polyethyleneimine - Lin, Peng; Jiang, Yingqiu; Ru, Xiaolin; Che, Wenbo; Zhang, Xiaochun; Ma, Lingfei; Hou, Junfeng; Yu, Youming (Frontiers in Materials, 2021)
To improve the flame retardancy of bamboo materials, layer by layer (LbL) self-assembly of phytic acid (PA)-polyethyleneimine (PEI) on the surface of shaving super bamboo specimens with different solution concentrations of PA-PEI and times of LbL self-assembly was completed in this study. Fourier transform infrared analysis results showed that PEI was well assembled to the surface of bamboo specimens by a hydrogen bond with PA as intermediation. The application of PA and PEI significantly promoted the formation of carbon residue, as characterized by simultaneous thermal measurements. Particularly, the peak heat release rate and total heat release rate of bamboo self-assembly with 10 wt% PA and 10 wt% of PEI solution were reduced by 19.36 and 22.3%, respectively. The treated bamboo specimen showed increases of 35.56 and 480.70% in fire performance index and residual mass, respectively, compared to the control sample. Besides, yields of CO and CO2 were decreased by 17.77 and 17.07% in comparison with the control group, respectively. The LbL self-assembly with PA-PEI can effectively improve the flame retardancy of bamboo materials by promoting the formation of a residual char layer.